HUBUNGAN ANTARA USIA MENIKAH DAN PARITAS PADA WUS DI RS PKU MUHAMMADIYAH YOGYAKARTA: The Relationship Between Age At Marriage And Parity In Wus At Pku Muhammadiyah Hospital Yogyakarta - fajila, nurul (LPPM - STIKES Pemkab Jombang, 2025)
Cervical cancer is a cancer that grows in the cells of the cervix which is 95% caused by the human papilloma virus and is transmitted through sexual intercourse. According to the World Health Generation (WHO), cervical cancer is the fourth most common cancer in women worldwide with around 660,000 new cases and around 350,000 mortality in 2022, the number of cancer patients in Indonesia in 2020 was around 396,914, and the highest cancer prevalence was in DI Yogyakarta (4.1‰) so that it ranks second with the most incidents after breast cancer in Indonesia. The purpose of this study is to determine the relationship between age of marriage and parity with the incidence of cervical cancer in women of childbearing age. The research method applied quantitative study with correlational method type. With an observational analytical design, a Cross-sectional study approach was implied. The sampling technique used Quota sampling. This study used 58 respondents. Univariate and bivariate data analysis was with the chi square test. Based on the results of the study, it can be concluded that there is a relationship between age of marriage and the incidence of cervical cancer at the PKU Muhammadiyah Yogyakarta Hospital; the chi square statistical test obtained a value of ? value = 0.025. married at age <20 years have a risk 4 times higher compared to women who marry at age ?20 years. In addition, is arelationship between Parity and the incidence of cervical cancer in women of childbearing age at PKU Muhammadiyah Yogyakarta Hospital, and Chi Square statistical test obtained a value of ? value = 0.045, parity >3 has a risk 0.287 greater than parity ?3.